On the way to diploidization and unexpected ploidy in the grass Sporobolus section Spartina mesopolyploids - Armel Salmon; Yan Hao; Morgane Milin; Oscar Lima; Armand Cavé-Radet; Delphine Giraud; Corinne Cruaud; Karine Labadie; Benjamin Istace; Caroline Belser; Jean-Marc Aury; Patrick Wincker; et al. (Nature Communications)
Abstract Plant history is characterized by cyclical whole genome duplication and diploidization with important biological and ecological consequences. Here, we explore the genome history of two related iconic polyploid grasses (Sporobolus alterniflorus and S. maritimus), involved in a well-known example of neopolyploid speciation. We report particular genome dynamics where an ancestral Sporobolus genome (n = 2x = 20) duplicated 9.6-24.4 million years ago (MYA), which was followed by descending dysploidy resulting in a genome with an unexpected base chromosome number (n = 15). This diploidized genome duplicated again 2.1-6.2 MYA to form a tetraploid lineage (2n = 4x = 60), thus reshuffling the ploidy of these species previously thought hexaploids. We also elucidate the mechanism accompanying the speciation between S. maritimus (2n = 60) and S. alterniflorus (2n = 62), resulting from chromosome restructuring, and identify key adaptive genes in the corresponding regions. This represents critical findings to decipher molecular mechanisms underlying species expansion, adaptation to environmental challenge and invasiveness.